Adaptasi Kebiasaan Baru Selama Covid-19 dalam Pemanfaatan Sumberdaya Peternakan dan Pertanian Desa Peguyangan - Sukron Muttaqin; Siti Khoziah; Siti Alpiyah; Yulia Eka Nurjanah; Zumrotun Ni’mah; Ayu Risqiana; Aulia Safira Darmawan; Rika Zahera (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
Peguyangan village has potential in agriculture and animal husbandry. However, this potential has not been optimally utilized. This activity has main objective of recommending the community empowerment programs to optimize insight in to COVID-19 prevention and utilization of livestock and agriculture resources in the face of adapting new habits during COVID-19 pandemic. This agtivity wa carried out from 9 July to 22 Agustus 2020. Peguyangan Village has the potential to be a center for buffalo farming ang must continue to be developed. Keywords: chilies, shallots, siwang, telang